2018
DOI: 10.1097/gox.0000000000001832
|View full text |Cite
|
Sign up to set email alerts
|

Stress Distribution Patterns within Viscero- and Neurocranium during Nasoalveolar Molding: a Finite Element Analysis

Abstract: Background:The purpose of this study was to evaluate the stress distribution patterns within the viscero- and neurocranium of neonates during nasoalveolar molding.Methods:Finite element models of 3 different healthy neonates at different times of life (date of birth, 4 weeks, and 3.5 months) were generated on the basis of computed tomography scans. A validated workflow, including segmentation, meshing, setting of boundary conditions, and implementation of a bone density–dependent material model, was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In cases of NAM therapy, the procedure was started within the first two weeks of life and with respect to a corrected age in the case of preterm birth. 2 NAM therapy consisted of alveolar molding (6–8 weeks) and subsequent nasal molding (until operation). 14 , 22…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of NAM therapy, the procedure was started within the first two weeks of life and with respect to a corrected age in the case of preterm birth. 2 NAM therapy consisted of alveolar molding (6–8 weeks) and subsequent nasal molding (until operation). 14 , 22…”
Section: Methodsmentioning
confidence: 99%
“… 1 But NAM therapy should not be started too early and must be adapted in preterm birth because undesired force conduction to the anterior skull base might occur. 2 NAM is commonly performed according to the treatment algorithm described by Grayson et al, but several modifications are also reported in the literature, including CAD/CAM solutions. 3 6 …”
Section: Introductionmentioning
confidence: 99%